Performance accountability of public agencies in the act government - Prof. Abd. Rahman (Indonesia Prime, 2017)
Performance accountability of public bodies meaning widespread not only limited liability in law but also in the field of non-law. Special accountability law, imaged through the performance creation of the law (legal creating), as well as in the implementation of the law (legal applying) as the embodiment of government action (Bestuurhandeling). In the concept of the law of State administration and administrative law, Government action in question is the Act or acts committed by State administration in carrying out the task of Government.